Statistical mechanics of DNA melting in confined geometry - Mohanta D.; Giri D.; Kumar S. (My University, 2025)
Using exact enumeration technique, we studied the effect of asymmetry arising due to the cone-shaped channel on the DNA melting. We calculate the free-energy barrier arising due to this asymmetry, and its dependence on the base-pair interaction (say, solvent of different dielectric constants) across the interface. We also calculate the equilibrium properties of DNA to analyse the effect of base-pair interactions and nature of pore (cone versus flat) on dsDNA chain attached at varying distances from the edge of a pore. The simple model presented here captures the essential physics of transfer of dsDNA across the interface of the confined geometry. © 2019 IOP Publishing Ltd and SISSA Medialab srl.